WEB-BASED CLUSTER OPTIMIZATION USING K-MEDOIDS AND DAVIES BOULDIN INDEX - Ryan Christian; Deny Jollyta (STMIK Royal, 2022)
Abstract: Clustering data has always been a fascinating subject to research numerous perspectives. A variety of knowledge is produced by the calculating process utilizing various algorithms. The genesis of cluster optimization is based on differences of opinion about the cluster's results. In general, cluster and optimization findings are generated using software such as Matlab, RapidMiner, and programming languages like Python. Users, however, have not been satisfied with the results so far. The various outcomes are the primary motivations for continuing to create and develop applications. The goal of this research is to create an application that can evaluate cluster data using the K-Medoids method, which can then be further optimized using the Davies Bouldin Index (DBI). Because the target application is students and lecturers who use it in learning and observers of the cluster field, the application can indeed be accessible through a browser to make it easier to use. For ease of using it, the program is available on both desktop and mobile platforms. Through separately created applications, it is intended that this research will give an alternative to clustering and optimization. Keywords: application, cluster, dbi, k-medoids, optimization Abstrak: Clusterisasi data selalu menjadi topik yang menarik untuk dikembangkan dari berbagai sisi. Proses perhitungannya yang menggunakan berbagai algoritma menghasilkan knowledge yang beragam. Perbedaan pendapat terhasil hasil cluster menjadi dasar munculnya optimalisasi cluster. Umumnya hasil cluster dan optimalisasi diperoleh dari pengolahan menggunakan aplikasi yakni Matlab, RapidMiner, dan bahasa pemrograman seperti Pyhton. Namun demikian hasil yang muncul belum mampu memuaskan pengguna. Hasil yang berbeda menjadi alasan utama pembuatan maupun pengembangan aplikasi masih terus dilakukan. Penelitian ini bertujuan untuk membangun sebuah aplikasi yang dapat memproses data cluster menggunakan algoritma K-Medoids untuk selanjutnya dioptimalisasi dengan Davies Bouldin Index (DBI). Untuk memudahkan penggunaan, aplikasi dapat diakses pada browser karena target aplikasi adalah mahasiswa dan dosen yang menggunakan pada pembelajaran serta pemerhati bidang cluster. Aplikasi dirancang pada platform desktop dan mobile demi memudahkan pengaksesan. Diharapkan, penelitian ini memberikan alternatif dalam proses clusterisasi dan optimalisasi melalui aplikasi yang dirancang mandiri. Kata kunci: aplikasi; cluster; dbi; k-medoids; optimalisasi